2020
DOI: 10.3389/fbioe.2020.00413
|View full text |Cite
|
Sign up to set email alerts
|

Elastin-Like Recombinamer Hydrogels for Improved Skeletal Muscle Healing Through Modulation of Macrophage Polarization

Abstract: Large skeletal muscle injuries, such as a volumetric muscle loss (VML), often result in an incomplete regeneration due to the formation of a non-contractile fibrotic scar tissue. This is, in part, due to the outbreak of an inflammatory response, which is not resolved over time, meaning that type-1 macrophages (M1, pro-inflammatory) involved in the initial stages of the process are not replaced by pro-regenerative type-2 macrophages (M2). Therefore, biomaterials that promote the shift from M1 to M2 are needed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 65 publications
3
33
0
Order By: Relevance
“…This indicated an inverse correlation between cleavage kinetics and macrophage content, with no differences upon conjugation with the QK-peptide. In addition, the M1/M2 ratio confirmed an equilibrated presence of both types of macrophages with a slight tendency towards pro-healing macrophages (M2) over time, and without signs of chronic inflammation or fibrotic tissue formation, in agreement with previously described protease-sensitive ELR hydrogels [20,25]. Thus, in terms of macrophage-related immunogenicity, these hydrogels and scaffolds can be safely used for TERM applications that require the formation of a complex vascular structure.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…This indicated an inverse correlation between cleavage kinetics and macrophage content, with no differences upon conjugation with the QK-peptide. In addition, the M1/M2 ratio confirmed an equilibrated presence of both types of macrophages with a slight tendency towards pro-healing macrophages (M2) over time, and without signs of chronic inflammation or fibrotic tissue formation, in agreement with previously described protease-sensitive ELR hydrogels [20,25]. Thus, in terms of macrophage-related immunogenicity, these hydrogels and scaffolds can be safely used for TERM applications that require the formation of a complex vascular structure.…”
Section: Discussionsupporting
confidence: 86%
“…This technique has reported the formation of biocompatible ELR hydrogels [20] that promoted the regeneration of different tissues, thanks to their bioinspired ECM-like nature and to the inclusion of bioactive sequences [21]. For instance, they have shown to enable the regeneration of bone [22], cartilage [23,24], skeletal muscle [25], cornea [26] and cardiovascular tissues [27][28][29]. In addition, ELRs have demonstrated a non-immunogenic response, promoting the shift from type-1 macrophages (M1, pro-inflammatory) towards type-2 macrophages (M2, pro-regenerative), thus preventing fibrosis and inducing an improved healing of the damaged tissue [25].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…growth factors, RGD domains, and ECM proteins. Recombinantly produced biomaterials such as the elastin-like recombinamer polymer allows for the precise composition of structural and chemical properties, with gene technology introducing sequences for cell attachment and MMP degradation and at the same time exposing functional groups for binding of for example growth factors to promote or maintain the MSC therapeutic effect (Ibáñez-Fonseca et al, 2020). De Santis et al recently demonstrated the functional outcome of a 3D bioprinted hybrid hydrogel combining decellularized lung tissue with alginate to form human airways containing primary human airway epithelial progenitor cells (De Santis et al, 2020).…”
Section: Hydrogel Encapsulationmentioning
confidence: 99%
“…Catalyst-free click reactions occured on mixing these ELPs, yielding a hydrogel. The click hydrogels, with cell-adhesive and biodegradable properties, were successful in tissue regeneration, in animal models of volumetric muscle loss [ 14 ], myocardial infarction [ 15 ], and critical limb ischemia [ 16 ].…”
Section: Introductionmentioning
confidence: 99%